Television Demands Professionalism, Taste, And Level Of Expertise - Hojimatov Doston Hamidulla ogli (Peerian Journals Publishing, 2025)
This article discusses the highly skilled professionals in the field of television, as well as emerging creators entering the industry. In television, having high potential and refined taste plays a significant role. The results show that, in television, the teacher-student tradition and the acquisition of knowledge in the field is crucial to mastering the craft.
Keywords: State television channels; Non-state television channels; Entertainment shows